Comparison of fatty acids profile of the gonads and eggs of Lutjanus guttatus (Perciformes: Lutjanidae) obtained from wild and captive broodstock - Jonathan Chacón-Guzmán; Milagro Carvajal-Oses; Pedro Toledo-Agüero; Héctor Flores-Gatica (Uniciencia, 2020)
The proportions of fatty acids present in eggs and gonads of wild and captive Lutjanus guttatus (Steindachner, 1869) were evaluated to assist in obtaining nutritional information necessary to improve the diets provided in aquaculture production centers of this species. Samples of eggs and gonads were obtained from broodstock (1.0±0.1 kg) kept in the Pacific Marine Park (PMP), Costa Rica, and from individuals caught by fishermen in their natural environment.  The samples were taken in triplicate during the period spanning from August to September 2015.  Captive snappers were fed a fresh diet. Spawns and gonads were obtained from two groups of 16 specimens each of captive and wild fish, both groups having a sex ratio of 1:1 male to female. Gonads from females were selected according to their maturity stage, and male gonads were sampled based on the quantity, viscosity and color of semen. There were no statistically significant differences (p≥0.05) between egg diameters and oil droplets size; viability rates, expressed as percentages, were considered to be high and appropriate for comparison (91.2% captive, 86.1% wild).  There were also no statistically significant differences in the fatty acid composition of eggs obtained from wild and captive females (p=0.2188), or in gonads from males (p=0.6179) and wild and captive females (p=0.1153). The presence of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) was observed in all of the samples analyzed, while arachidonic acid (ARA) was found in amounts ranging from 0.38 to 5.07% and was not present in the eggs of wild females or in the gonads of captive females.